Conceptual-Cognitive Influence of The Structure of English and Uzbek Vocabulary and Possibilities of Text Formation - Eshkobilova Ozoda Khalikulovna (Web of Journals Publishing, 2023)
This article delves into the intricate interplay between the structural nuances of the English and Uzbek vocabularies and their profound impact on conceptual-cognitive processes, particularly in the realm of text formation. By examining the lexical, syntactic, and semantic characteristics unique to both languages, this study unravels the cognitive underpinnings that guide the creation of texts in English and Uzbek. The exploration of this dynamic relationship sheds light on how language structures mold cognitive frameworks, ultimately shaping the thought processes and expressive capacities of individuals within these linguistic landscapes. This research not only offers a comprehensive insight into the cognitive dimensions of multilingualism but also provides a nuanced understanding of how linguistic structures influence the construction of meaning in diverse cultural and communicative contexts.
Keywords: Conceptual-Cognitive Influence; English Vocabulary; Uzbek Vocabulary; Text Formation; Language Structure.